Silencing LINC00663 inhibits inflammation and angiogenesis through downregulation of NR2F1 via EBF1 in bladder cancer - Xiulong Zhong; Lijiang Sun; Junxiang Liu; Xiaokun Yang; Minghui Hou; Xinning Wang; Huifeng Diao (RNA Biology)
This study is to elucidate the effect of the LINC00663/EBF1/NR2F1 axis on inflammation and angiogenesis in bladder cancer (BC) and related molecular mechanisms. After transfection, functional experiments were conducted to test cell proliferation and invasion, tube formation ability, and content of inflammatory factors, Snail, E-cadherin, and VEGFA. Meanwhile, the relationships among LINC00663, EBF1, and NR2F1 were predicted and verified. In addition, xenograft experiments in nude mice were performed to observe the oncogenicity of 5637 BC cells in vivo. In BC tissues and cells, LINC00663 and NR2F1 were upregulated. Silencing NR2F1 or LINC00663 repressed cell proliferation and invasion, weakened vascular mimicry in vitro, decreased inflammatory factor, Snail, and VEGFA levels, and increased expression of E-cadherin. LINC00663 positively regulated NR2F1 expression through EBF1. Additionally, in vivo experiments showed that NR2F1 upregulation reversed the suppression effects of LINC00663 silencing on tumour growth, inflammation, and angiogenesis. Silencing LINC00663 decreased NR2F1 expression by mediating EBF1, thereby inhibiting BC inflammation and angiogenesis.